Business Analysis of Plant Factories Using the Business Model Canvas - Malik, Maulana; Thamrin, Muhammad; Bin Haimid, Mohd Tarmizi (Jurnal Dinamika Sosial Ekonomi, 2024)
A plant factory is a production system that operates in a controlled environment, where factors important for plant growth, such as light, temperature, CO2, and humidity, are artificially regulated. The system is also equipped with automated mechanisms for controlling fertilization and irrigation, as well as maintaining clean conditions for plants. The purpose of this study is to develop a business model canvas for a warehouse plant factory in MARDI, Serdang, Selangor, Malaysia. This research uses a descriptive qualitative approach method. In analyzing the warehouse plant factory business using the Business Model Canvas (BMC) method, this business model has significant prospects in overcoming the technology and knowledge gap in the agricultural sector. The successful implementation of this business model is largely determined by the alignment between the application of modern technology and the socio-economic conditions of farmers in the local area.